Cognitive and functional deficits in bipolar disorder and schizophrenia as a function of the presence and history of psychosis. (18th May 2018) - Bowie, Christopher R; Best, Michael W; Depp, Colin; Mausbach, Brent T; Patterson, Thomas L; Pulver, Ann E; Harvey, Philip D
Abstract : Objectives: Schizophrenia and bipolar disorder overlap considerably. Schizophrenia is a primary psychotic disorder, whereas approximately half of people with bipolar disorder will experience psychosis. In this study, we examined the extent to which cognitive and functional impairments are related to the presence and history of psychosis across the two disorders. Method: A total of 633 participants with bipolar disorder I, schizophrenia, and schizoaffective disorder were recruited for a study on the genetics of cognition and functioning in bipolar disorder and schizophrenia. Participants were classified into five groups: bipolar disorder with current psychosis (N = 30), bipolar disorder with a history of psychosis (N = 162), bipolar disorder with no history of psychosis (N = 92), schizophrenia with current psychosis (N = 245), and schizophrenia with past psychosis (N = 104). Results: Cognitive profiles of all groups were similar in pattern; however, both current psychosis ( P < .02) and a diagnosis of schizophrenia ( P < .03) were associated with greater impairment. Schizophrenia with current psychosis was also associated with a superimposed severe impairment in processing speed. Both psychosis ( P < .03) and schizophrenia diagnosis ( P < .01) were associated with poorer functional competence. Individuals with bipolar disorder and schizophrenia experienced similar impairments in real‐world functioning if they were experiencing current psychosis ( P = .32). Conclusion: The presence of active psychosis is an important cross‐diagnostic factor in cognition and functioning in both schizophrenia and bipolar disorder. Characterization and treatment of cognition and functional deficits in bipolar disorder should consider the effects of both current and history of psychosis.